Effect of Parity and Stage of Gestation on Maternal Growth and Feed Efficiency of Gestating Sows - L. L. Thomas; R. D. Goodband; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2017)
The objective of this study was to evaluate the effect of parity and stage of gestation on maternal weight gain and efficiency of feed use in group-housed gestating sows from a commercial sow farm. A total of 712 females (Camborough, PIC, Hendersonville, TN) were group-housed from d 5 to 112 of gestation and individually fed with electronic sow feeders (ESF). Feed intake and BW were recorded daily throughout gestation via the ESF and a scale located in an alleyway just after sows exited the feeding station. Gilts (parity 1) and sows received 6.5 and 7.3 Mcal ME per d. Maternal weight gain, not including products of conceptus, and feed efficiency were predicted using a series of equations to model nutrient utilization in gestation. Data were divided into 3 parity groups: 1, 2, and 3+, and gestation was divided into 3 periods: d 5 to 39, 40 to 74, and 75 to 109. After dividing energy requirements into tissue pools for maintenance, growth (maternal protein and fat deposition) and products of conceptus, the greatest portion of the energy requirement was for maintenance and maternal growth. The predicted energy used for maternal protein and fat deposition decreased (P<0.05) in each period of gestation, regardless of parity group. Parity 2 sows had the greatest (P<0.05) energy use for maternal protein and fat deposition in all stages of gestation while parity 1 sows had a negative energy balance during the final stage of gestation. Parity 1 sow maternal BW increased (P<0.05) in each period of gestation; however, parity 2 and 3+ sow maternal BW remained static after d 74 of gestation. Parity 3+ sows had the greatest (P<0.05) maternal BW throughout the course of gestation in comparison to other parity groups. Regardless of parity, maternal ADG decreased (P<0.05) from d 39 to 74 before increasing (P<0.05) during the final stage of gestation. Parity 1 sows had the greatest (P<0.05) ADG in all gestation periods. Parity 1 sow G:F decreased (P<0.05) in each sequential period of gestation. Parity 2 and 3+ sow G:F decreased (P<0.05) from d 39 to 74 but improved (P<0.05) during the final period of gestation. Parity 1 sow G:F was greater than parity 2 and 3+ sows in most gestation periods. Overall, this study demonstrates how feed usage, stage of gestation, and parity affect sow maternal BW and tissue pool composition in highly prolific sows.
Keywords: maternal growth; gestation; sows